Production potential and economics of mung bean in rice based cropping pattern in Sylhet region under AEZ 20 (Bangladesh Journal of Agricultural Research, 2017)
The study was conducted at the farmers field in Sylhet under AEZ 20 during three consecutive years 2012-13, 2013-14 and 2014-15 to determine the productivity and profitability of cropping patterns viz., IP: improved pattern (Mung bean-T. aus-T. aman rice) and FP: farmer’s pattern (Fallow-T. aus-T. aman rice) through incorporation of high yielding varieties and improved management practices. The experiment was laid out in randomized complete block design with six dispersed replications. Results showed that the improve pattern with management practices provided 10.85 and 14.32% higher grain yield of T. aus and T. aman rice, respectively; also contributed more T. aman mean rice equivalent yield (11.81 t ha-1) compared to farmer’s pattern. Mean sustainable yield index (77.63%), production efficiency (47.88 kg ha-1day-1), and land use efficiency (67.66%) were maximum in Mung bean-T. aus- T. aman rice cropping system. Similarly, the highest mean gross margin (Tk.126762 ha-1) with benefit cost ratio (2.10) was obtained from improved pattern. Three years results revealed that 42% extra cost provides an ample scope of considerable improvement of the productivity of improved pattern with the inclusion of Mungbean before T. aus rice.Bangladesh J. Agril. Res. 42(3): 413-424, September 2017